ASSESSMENT OF THE RELIABILITY OF ELECTROMECHANICAL SYSTEMS WITH INCOMPLETE SPECIFICATION OF INITIAL DATA (Spectrum Journal of Innovation, Reforms and Development, 2025)
Modern complex electromechanical systems (hereinafter referred to as the system) are characterized by a more complex connection structure and increased requirements for the reliability of components. Moreover, advanced systems are quite unique and (or) smallbatch, and their constituent elements are basically miniature or expensive, so the direct use of engineering methods based on the processing of statistical data in determining the reliability indicators of systems is not possible.